Transdermal monitors to assess alcohol consumption in real-time and real-life – a qualitative study on user-experience. (4th July 2019) - Caluzzi, Gabriel; Pennay, Amy; Cook, Megan; Wright, Cassandra; Norman, Thomas; Kuntsche, Emmanuel
Abstract: Introduction: Transdermal alcohol monitors, such as Secure Continuous Remote Alcohol Monitors (SCRAMs), enable continuous measurement of alcohol consumption in participants' natural environments free from recall bias and response burden. This paper explores young research participants' experience of wearing SCRAMs to provide insights into the potential of the devices to be used for research on a larger scale. Method: In south-east Australia, participants were recruited among festival attendees ( n = 12) and college students ( n = 18). Participants wore the SCRAMs over 3–4 days, and upon returning the devices participated in a semi-structured qualitative interview about their experiences of the devices. Results: Most participants reported becoming unaware of the device after initial adjustment and did not believe their drinking patterns had been altered by wearing the SCRAM. Perceived similarities with correctional monitoring equipment led to a number of social interactions with onlookers, but participants generally felt at ease with this. Common issues reported by participants related to the physical discomfort and restrictions caused by the devices, citing problems with sleeping, exercising, and irritation with the clamping mechanism as impediments. Conclusions: Although SCRAMs have not been designed with research purposes in mind, this study highlights their utility in measuring alcohol consumption in real-life and real-time. Most participants suggested that their drinking patterns were unaffected and that any physical discomfort was manageable; however, comfort is a critical consideration in terms of improving the user experience. Adequately controlled validation studies are needed to determine if and how wearing SCRAMs affects retention, behaviour and drinking patterns.